Applying the CHIME recovery framework in two culturally diverse Australian communities: Qualitative results - Brijnath, Bianca (Sage Publications Ltd., 2015)
Background: CHIME (connectedness, hope and optimism about the future, identity, meaning in life and empowerment) is a framework for conceptualising personal recovery from mental illness. To date, there has been limited research on its cross-cultural applicability. Aims: To apply CHIME to two culturally diverse groups' conceptualisation of recovery from depression. Method: Qualitative interviews with 30 Anglo-Australians and 28 Indian-Australians living with depression in Melbourne, Australia. Data were thematically analysed. Results: Both groups valued connectedness but experienced stigma and struggled to broker family support. Identity, hope and optimism for the future were associated with positive thinking, being 'cured' and discontinuing treatment. Spirituality gave Indian participants meaning in life; Anglos derived meaning from the illness experience itself. Feeling empowered, for both groups, was related to improved socio-economic status and being 'settled' (e.g. having gainful employment, a home and family). Conclusions: CHIME was applicable in both groups, but culture mediated how cross-cutting issues (e.g. stigma) and sub-components of CHIME were operationalised. Recovery was also influenced by participant's socio-economic context. Research, policy and practice implications are discussed.